Aspectos generales del paciente felino geriátrico - Arcila , Victor (Spei Domus, 2005)
Modern life imply changes that conduce to choose pets that demand little attention by owners. On the other hand, advance in medical and therapeutic knowledgement and surgical skills has allowed that the life spin of domestic animals will be longer. The domestic cat show a clear tendency to be the pet of predilection due their independence. This is a specie that has been accompanied the man from old times and it should be approached with special attention because in spite of the physical resemblance with canines is different on the matter of their necessities, behavior and reproduction. The oldness is a physiologic state during which phisical and biochemical changes occur and diverse illness processes can be predisposed. Oldness in cats brings a series of physiologic changes on organic systems that conduce to changes on nutritional requirements. The veterinary should be prepared to assist a day to day higher volume of oldness patients (canines and felines).